Edukasi Metode Bercerita dalam Meningkatkan Semangat Belajar Al-Qur’an Para Santri - Ma’arif Syahim, Alwan; Sastra, Jufri; Ubaidillah, Muhammad; Fajri, Muhammad; Musthofa, Misbah; Hartono, Hardi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Education in the Qur'anic Education Park (TPQ) has an important role in shaping the younger generation who have Qur'anic expertise. this study aims to explore the positive influence of the positive reinforcement approach and storytelling method in increasing the enthusiasm of children at TPQ Al-Hikmah Surowono in memorizing the Qur'an. the research method uses a qualitative method with a case study approach, involving participatory observation and in-depth interviews with teachers and TPQ students. the results of this study can show that a positive approach can strengthen the liveliness that affects the achievement of students and the use of creative storytelling methods has a significant positive impact. The children can show increased enthusiasm in learning the Qur'an, getting more enthusiastic and actively involved in learning activities. in This approach also helps in building good relationships between teachers and students, creating an effective, fun, and supportive learning environment. In conclusion, the positive approach and storytelling method not only increase the spirit of the santri in memorizing the Qur'an but also create their learning experience at TPQ. This article advocates the use of this approach as an effective strategy in Qur'anic education at TPQ Al-Hikmah Surowono, promoting Santri-oriented learning and binding Islamic values in the local community.